Analysis of Traffic Congestion Levels on Hertasning Baru Street - Azriful, Azriful; Widiastuty, Lilis; Kahfi, Muhammad; Rusni, Eka (Public Health Science & Religion, 2024)
Background: Congestion is a problem that occurs in almost all corners of the world. In Indonesia, especially the capital city of Jakarta, the congestion rate is 34%, even though this percentage is still relatively high. Makassar itself as the provincial capital is included in the 10 most congested cities in Indonesia. The congestion occurred because the increase in the number of vehicles was not proportional to the road construction. This study aims to analyze the level of congestion on Aroepala street and Tun Abdul Razak street in 2022. Methods. The type of research used is a mixed method with a sequential explanatory design approach. A total of 16 informants were determined by purposive and snowball sampling techniques. Data collection was carried out by observation and interview techniques. Results. of the study show that after the opening of roundabout access in 2022, the level of congestion on Aroepala street is included in category (F), meaning that traffic is obstructed, low speed, volume above capacity, often experiencing congestion for a long time. Furthermore, the level of congestion on Tun Abdul Razak street is included in category (C), which means the flow is stable, the speed can be controlled. Conclusion. Congestion on Aroepala Street causes health problems felt by the community when experiencing congestion and is related to psychology and ergonomics.